If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -22 = 41 Reorder the terms: -22 + 7x = 41 Solving -22 + 7x = 41 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 7x = 41 + 22 Combine like terms: -22 + 22 = 0 0 + 7x = 41 + 22 7x = 41 + 22 Combine like terms: 41 + 22 = 63 7x = 63 Divide each side by '7'. x = 9 Simplifying x = 9
| 5*12+10=4*12+p | | 5*-12+10=4*-12+p | | 5-12+10=4*-12+p | | 83=32x+10 | | 18-12+2+1= | | 60-4x=32x+16 | | 8x+4=6x+10 | | -19.48+x=28.03 | | 3x+8=-8-7x | | 10-3h=25 | | y=-4x+0 | | 5t+1=11 | | 82-5x=22x+16 | | 4x-9=175 | | 11-7x=19-14x | | 6m+11=137 | | 9y-47=43 | | 2y=36 | | b+5=59 | | 9b+24=150 | | 3x-21=1479 | | x^3+x^2-8x-12=0 | | x*3-50=22 | | 6x-6=5.6 | | m^2=-17 | | 5x=28 | | 9x+6=-20 | | 5p^2=-27p-10 | | (2x-1)(2x-1)=49 | | (4x+3)(4x+3)=7 | | 98x^2= | | (x+5)(x+5)=20 |